2019
DOI: 10.3389/fpsyg.2019.02047
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Effort-Reward Imbalance Questionnaire for Teachers (Teacher ERIQ)

Abstract: The effort-reward imbalance (ERI) model is a theoretical model of a psychosocial work environment with adverse effects on health and well-being that focuses on a mismatch between high efforts spent and low rewards received at work. This study aimed to develop and psychometrically test an effort-reward imbalance questionnaire for teachers (Teacher ERIQ) based on the ERI model. The structure validity, reliability, and criterion validity of the new questionnaire’s scores were evaluated in a sample of 475 Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…In the context of public health emergencies, working conditions and stress-related factors are among the most important determinants of mental health status among public health workers facing demanding work. The effort–reward imbalance model (ERI) is commonly used in research on work stress and working conditions in many professional populations, such as nurses [ 16 ], teachers [ 17 , 18 ], police officers [ 19 ] and doctors [ 20 ]. Additionally, the ERI model has been widely used to predict many stress-related physical and psychological disorders, such as hypertension [ 21 , 22 ], depression [ 16 , 23 ] and anxiety [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of public health emergencies, working conditions and stress-related factors are among the most important determinants of mental health status among public health workers facing demanding work. The effort–reward imbalance model (ERI) is commonly used in research on work stress and working conditions in many professional populations, such as nurses [ 16 ], teachers [ 17 , 18 ], police officers [ 19 ] and doctors [ 20 ]. Additionally, the ERI model has been widely used to predict many stress-related physical and psychological disorders, such as hypertension [ 21 , 22 ], depression [ 16 , 23 ] and anxiety [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jachens et al (2019) found that ERI was positively related to emotional exhaustion and depersonalization but negatively related to reduced personal accomplishment. Similarly, Ren et al (2019) found a positive and significant relationship between ERI and emotional exhaustion, whereas ERI was not significantly related to depersonalization and perceived lack of personal accomplishment. Their findings indicated that the imbalance between pay and return directly caused individuals' emotional exhaustion, but it did not affect their self-evaluation and basic attitude toward work.…”
Section: Effort-reward Imbalance and Job Burnoutmentioning
confidence: 79%
“…This study adopted the EFR questionnaire developed by Ren et al (2019) , which consists of two components (effort and reward). Effort contains 14 items, and the reward contains 14 items.…”
Section: Methodsmentioning
confidence: 99%